2021
DOI: 10.1016/j.ijid.2021.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and serum concentration monitoring of bedaquiline in Chinese patients with multidrug-resistant tuberculosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…However, most of them were gentle and tolerant. QTc prolongation was widely concerning when Bdq was applied, but generally, it is not serious [29][30][31][32]. In our study, although the cases number with a QTc ≥ 450 ms in Bdq group were more than that in non Bdq, no one withdrew Bdq as a result of QTc prolongation.…”
Section: Discussioncontrasting
confidence: 48%
“…However, most of them were gentle and tolerant. QTc prolongation was widely concerning when Bdq was applied, but generally, it is not serious [29][30][31][32]. In our study, although the cases number with a QTc ≥ 450 ms in Bdq group were more than that in non Bdq, no one withdrew Bdq as a result of QTc prolongation.…”
Section: Discussioncontrasting
confidence: 48%
“…Compared with the standard regimen containing bedaquiline, QTc interval prolongation of more than 500 ms was found to be higher, between 6.2% and 25.6%. [37,38] A standard regimen includes fluoroquinolones (levofloxacin, moxifloxacin), clofazimine, and delamanid, potentially causing QT interval prolongation. Several studies have shown, although bedaquiline was associated with QTc prolongation, however, the grade of severity was low or middle, and no TdP or death-related cardiac arrhythmia was found.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular potassium correction to the normal range shortens the QT interval. [39] Myelosuppression and neuropathy are considered the important causes of temporally or permanent discontinuation of linezolid in a regimen. Hematologic toxicity due to linezolid was associated with mitochondrial disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous clinical studies confirm that the strong bactericidal and sterilizing activity of BDQ-containing regimen originally found in mouse models of TB ( 123 , 124 ). BDQ has demonstrated potent clinical activity against MDR-and XDR-TB complex strains ( 27 , 118 , 121 , 122 ). Importantly, BDQ-containing treatment regimens have showed improved outcomes rate over SLID-containing regimens for the treatment of patients with RR-/MDR-TB ( 120 ).…”
Section: Clinical Treatment Efficacy Of Bdqmentioning
confidence: 99%
“…Recently, the WHO suggested SLID be replaced in the standard STR with a BDQ-containing regimen. The recommended dose of BDQ is 400 mg orally once daily for 2 weeks followed by 200 mg orally three times weekly for 22 weeks and total duration of BDQ treatment was 24 weeks ( 117 , 118 , 120 ). Many studies have reported the use of BDQ favorable outcomes rates at week 24 of treatment exceeding 80% ( 15 , 117 ).…”
Section: Clinical Treatment Efficacy Of Bdqmentioning
confidence: 99%